Between Risk and Resistance: Gender Socialization, Equality, and Ambiguous Norms in Fear of Crime and Safekeeping. (April 2017) - van Eijk, Gwen
Gender socialization is a key factor in explaining gender differences in managing fear of crime and risks in public space. By emphasizing the continuing role of traditional norms that underline women's vulnerability and prescribe safekeeping, previous studies have ignored the role of increasing gender equality, alternative norms that prescribe women's independence and strength, and resistance to traditional norms. Based on in-depth interviews with 28 couples, this article explores women's ambivalence and resistance toward traditional norms, how talk and practice reflect mixed messages on how to "properly" do gender, and aligning as well as conflicting views and roles within couples.